Network governance w fińskim samorządzie terytorialnym: naturalny stan rzeczy czy wyzwanie dla lokalnej demokracji? - Radzik-Maruszak, Katarzyna (Polityka i Społeczeństwo, 2020)
The main aim of the article is to present the practice of network governance concept in Finnish local government and its impact on local democracy, including the role played by elected representatives. The main hypothesis of the study implies that the idea of network governing, not only forces municipal councils to redefine their roles, but also reduces the scope of their responsibilities and limits the level of accountability. The study is based on empirical research conducted in 22 municipalities located in Pirkanmaa Region, Southern Finland in Spring 2015. The results of the research indicate that although network governance easily fits into Finnish local government, the concept brings many challenges. One of the most important challenges is the necessity to strengthen the say of elected representatives, presently perceived with regard to governing process mainly as rubber-stamp councils.